Fomepizole for Ethylene Glycol and Methanol Poisoning - Brent, Jeffrey (The New England journal of medicine, 2009)
A 35-year-old man is brought to the emergency department after ingesting automobile antifreeze. His pH is 7.30, and his urinalysis reveals calcium oxalate crystals, findings consistent with ethylene glycol poisoning. Treatment with fomepizole is recommended. Fomepizole is a competitive inhibitor of alcohol dehydrogenase that prevents the formation of the toxic metabolites of ethylene glycol and methanol. A 35-year-old man is brought to the emergency department after ingesting automobile antifreeze. Treatment with fomepizole is recommended. Fomepizole is a competitive inhibitor of alcohol dehydrogenase that prevents the formation of the toxic metabolites of ethylene glycol and methanol. Foreword This Journal feature begins with a case vignette that includes a therapeutic recommendation. A discussion of the clinical problem and the mechanism of benefit of this form of therapy follows. Major clinical studies, the clinical use of this therapy, and potential adverse effects are reviewed. Relevant formal guidelines, if they exist, are presented. The article ends with the author's clinical recommendations. Stage A 35-year-old man is brought to the emergency department by his wife after ingesting automobile antifreeze in an attempt at self-harm. On presentation, the patient is somnolent. He is afebrile and has a blood pressure of 126/72 mm Hg, a pulse rate of 102 beats per minute, and a respiratory rate of 24 breaths per minute. Pulse oximetry shows a hemoglobin saturation of 97% while the patient is breathing ambient air. His physical examination is normal except for tachypnea. His serum electrolyte profile and creatinine level are normal except for a serum carbon dioxide level of 17 mmol per . . .